Frequency of antibodies against Toxoplasma gondii Cebus apella monkeys raised in captivity - Chávez V., Amanda (2005)
The purpose of the present study was to determine the frequency of primates (Cebus apella) carrying anti-Toxoplasma gondii antibodies at the zoo of the Patronato del Parque de las Leyendas, in Lima. Sixty two sera samples were obtained and analyzed by the Indirect Hemaglutination test (HAI) to detect antibodies against T. gondii. The results showed that 90.3% (56/62) sera were positive, and no significant asociation due to sex and age (juvenile and adult) were found. The high rate of positive primates to this parasite could be due to the high number of domestics cats in the premises.